What Augmented Reality Would Face Today? The Legal Challenges to the Protection of Intellectual Property in Virtual Space - Indriani, Masitoh; Liah Basuki Anggraeni (Media Iuris, 2022)
AbstractAugmented Reality (AR) refers to a display of a real-world environment whose elements are augmented by one or more layers of text, data, symbols, images, or other graphical display elements. AR technology is always associated with online games. Beyond online gaming, AR has become part of daily life and affects every aspect of how society interacts with technology. In retail and marketing, AR and other virtual technologies play a very important role in saving costs. AR is also used in the education and medical sector, also in preventing crime. AR is even further used for humanitarian activities to reach remote areas affected by natural disasters and save human lives. Considered a new technology, the commercialization of AR may bring incredible business opportunities as well as potential legal risks. In the context of Intellectual Property (IP), AR systems and services can embody a variety of forms of IP. Meanwhile, the operation of AR systems in virtual spaces is creating issues about how to deal with data breaches and privacy. By using doctrinal methods, this paper will explore the legal challenge of AR in the context of IP protection in the virtual space and investigate the potential liability caused by the failure of AR systems from the Indonesian legal perspective.Keywords: Augmented Reality; Intellectual Property; Legal; Virtual Space.